Advancing Regulations and Harmonizing Laws to Ensure Fair and Transparent Legal Certainty in Bribery and Gratification Cases - Andin Wisnu Sudibyo; Megawati Barthosr (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
This study aims to analyze the application of laws and regulations relevant to the topic discussed by employing a normative legal research method. Normative legal research is a method focused on the study of legal norms, doctrines, and principles found in legislation and scholarly writings. In this study, two main approaches are applied: the statute approach and the conceptual approach. The statute approach involves a systematic examination of legal provisions found in various legal instruments, including laws, government regulations, ministerial regulations, and other related legal sources. By analyzing these written norms, the research seeks to identify the legal basis that governs the issue under study. This approach enables the researcher to determine the extent to which existing regulations are relevant, consistent, and effectively implemented in addressing the legal problem. Meanwhile, the conceptual approach is used to explore the legal theories, principles, and definitions that underlie the legal rules being analyzed. This approach allows the study to go beyond the textual interpretation of law and delve into the conceptual framework that gives meaning to legal provisions. It includes an analysis of key legal doctrines, theoretical perspectives, and fundamental legal concepts such as justice, legal certainty, and legal responsibility. Combining these two approaches provides a comprehensive understanding of how the law is both applied and interpreted in the context of the research topic. It helps uncover inconsistencies, gaps, or overlaps in the regulatory framework, and also facilitates a deeper reflection on the rationale behind the law. Moreover, this methodology allows for the formulation of constructive legal arguments and recommendations, based on a sound interpretation of legal norms and principles.